Comparing pulse amplitude modulated (PAM) fluorometry with radiocarbon technique for determination of inorganic carbon fixation in Chlorella vulgaris (Trebouxiophyceae, Chlorophyta). Issue 1 (2nd January 2022) - Camargo, Eduardo Caffagni; Rossi, Raquel Andrade; Silva, Jaqueline Carmo; Miwa, Adriana Cristina Poli; Prášil, Ondřej; do Carmo Calijuri, Maria; Lombardi, Ana Teresa
ABSTRACT: Integration of pulse amplitude modulated (PAM) fluorometry and conventional methods for estimating carbon assimilation in microalgae is important for physiological, ecological and economic purposes. In this study, we compared PAM fluorometry and carbon-14 ( 14 C) uptake techniques to estimate the carbon fixation rate in Chlorella vulgaris under controlled laboratory conditions. The key parameter for this comparison was the electron yield for carbon fixation ( Фe ), commonly assumed when converting electron transport rate ( ETR ) values into the chlorophyll-specific carbon fixation rate ( P B ). Additional analyses of maximum ( ΦM ) and effective ( Φ'M ) quantum efficiency of photosystem II, photochemical ( qP ) and non-photochemical ( NPQ ) quenching, and photosynthesis-irradiance response curves demonstrated that the photophysiology of C. vulgaris did not change after a 2-h incubation with NaH 14 CO3 and Na2 CO3 (control). The association of P B obtained through the 14 C method (151 ± 8.77 µmol C [mg chl a ] –1 h –1 ) with ETR (411 ± 3.91 µmol e − [mg chl a ] –1 h –1 ) resulted in an average Фe of 0.37 ± 0.02 µmol C [µmol e − ] –1, which is higher than theoretical Фe values usually reported in the literature (e.g. 0.20 and 0.25). We attributed this discrepancy to a possible inaccuracy in ETR due to underestimated values of chlorophyll-specific absorption cross-section ( a* ) and the common assumption that only 50% of total light is absorbed by photosystem II. We here demonstrate the importance of associating chlorophyll fluorescence with other primary production techniques, so that adjustments to calculation procedures can be made in accordance to species-specific physiological traits and particularities regarding culturing conditions.